(untitled) (TEST Trento Student Law Review, 2024)
In this article, we will analyze the importance of the Most Favored Nation (MFN) treatment standard in the context of international investment law as an instrument to create equal competition between foreign investors. We will investigate the history of this standard, and the changes it underwent during different moments of history. Our aim, through this article, is to understand how this standard has supported the liberalization of world trade. In furtherance of the aim, we will analyze the connection between the two relative standards, the National Treatment Standard and the Most- Favored-Nation Treatment Standard, as they are both used to create an equal playing field among foreign investors, and between foreign and national investors. We will examine the most important MFN clauses in different investment law agreements and analyze their main components and differences, together with the exceptions and limits of some MFN clauses. We will then focus on some of the most important decisions regarding the possibility of extending a Tribunal’s jurisdiction through an MFN clause and shortening the waiting periods. Our aim through this article is to understand how this standard has supported the liberalization of world trade.